Does the Role of Supervisors Determine Doctoral Students’ Success? - Budi Santoso; Indra Fahrizal; Marsofiyati Marsofiyati; Agus Wibowo (JPBM (Jurnal Pendidikan Bisnis dan Manajemen), 2021)
The purpose of this study was to analyse the effect of the role of supervisor and procrastination on the success of doctoral studies. The sample of this research was 149 alumni of the doctoral program in Indonesia who are taken randomly. A causal study using SEM PLS was implemented with Multi Group analysis (MGA) based on work groups between lecturers and non-lecturer employees. The results of this study indicated that the role of supervisor has a positive effect on the success of the study both as a whole and per group. The role of supervisor has a positive and significant effect on overall procrastination, but differs within the group, for lecturers it is not significant while for non-lecturers is significant. Procrastination as a whole sample has no significant effect on the success of doctoral study, as well as within the group. This can be concluded that the supervisor's role plays an important role in increasing the success of doctoral students' studies.Keywords: Success of study, role of supervisor, Procrastination.